PEMILIHAN KONSTRUKSI POLA CULOTTE PADA BAHAN KATUN: cullote, construction, cotton - Atiqah, Atiqah (Buana Pendidikan, 2010)
Higher technology and development of knowledge influences on clothing, that is not only for showing someone identity, it is also used for increase someone confidence. One of interesting and stylist cloth is cullote. Cullote is a cloth that is resemble a skirt, so it looks like a skirt. Making of cullote can be done by some patterns, such as MH Wancik system, Porrie Mulliawan, PSMI, JHC Meyneke, and so on. Not all of them system can be used for making comfortable cullote. Choosing the material influences ready-made cullote as well. The material used is cotton which has medium texture but not strict. This research is experiment research to know the influence of pattern on ready-made cullote. Pattern used are MH Wancik ad PSMI system. Data analysis as observation guide is T-test to find the different between MH Wancik and PSMI cullote, and to find the influence of choosing cotton as material of ready-made cullote. Based on data analysis, it gained P > 0,05, that there is a different between MH Wancik and PSMI system. It means there is influence pattern of cotton cullote. In the PSMI system has average about 4,2. While MH Wancik system’s average is 3,5. So it can be concluded that pattern of PSMI system, the mean is larger of pattern, is better than MH Wancik cotton cullote.